TI_GERICHTE 12.2007.128 vom 6. März 2008 , Assistenza giudiziaria: ricorso contro dinieto per mancanza di fumus boni juris - TI Tribunale d'appello (2008)
Assistenza giudiziaria: ricorso contro dinieto per mancanza di fumus boni juris